Nanoparticle-Based Lateral Flow Biosensor Integrated With Loop-Mediated Isothermal Amplification for Rapid and Visual Identification of Chlamydia trachomatis for Point-of-Care Use - Chen, Xu; Zhou, Qingxue; Tan, Yan; Wang, Ronghua; Wu, Xueli; Liu, Jiangli; Liu, Rui; Wang, Shuoshi; Dong, Shilei (Frontiers in Microbiology, 2022)
Chlamydial infection, caused by Chlamydia trachomatis, is the most common bacterial sexually transmitted infections, and remains a major public health problem worldwide, particularly in underdeveloped regions. Developing a rapid and sensitive point of care (POC) testing for accurate screening of C. trachomatis infection is critical for earlier treatment to prevent transmission. In this study, a novel diagnostic assay, loop-mediated isothermal amplification integrated with gold nanoparticle-based lateral flow biosensor (LAMP-LFB), was firstly devised and applied for diagnosis of C. trachomatis in clinical samples. A set of LAMP primers based on the ompA gene from 14 C. trachomatis serological variants (serovar A-K, L1, L2, L3) was successfully designed and used for development of C. trachomatis-LAMP-LFB assay. The optimal reaction system can be performed at a constant temperature 67℃ for 35 min. the total assay process, including genomic DNA extraction (approximately 15 min), LAMP reaction (35 min), and LFB readout (approximately 2 min), could be finished within 60 min. The C. trachomatis-LAMP-LFB could detect down to 50 copies per milliliter, and the specificity was one hundred percent, no cross-reactions with other pathogens were observed. Hence, our C. trachomatis-LAMP-LFB was a rapid, reliable, sensitive, cost-effective, and easy-to-operation assay, which could offer an attractive POC testing tool for chlamydial infection screening, especially in resource starvation settings.